Access to higher education and its socio-economic impact among Bedouin Arabs in Southern Israel. (2016) - Abu-Saad, Ismael
Highlights: Higher education has an important socioeconomic impact on minority development. Numerous policies restrict access to higher education for Bedouin Arabs in Israel. The public educational services provided to the Bedouin Arabs are sub-standard. Access to higher education is hampered by biased admission screening measures. Lack of financial aid for higher education is a barrier for Bedouin Arab students. Abstract: This paper explores minority access to higher education in Israel in general, and among the Negev Bedouin Arabs, in particular. The Negev Bedouin community has undergone major changes during the past 60 years, and has the lowest socio-economic level of any population group in Israel. Higher education plays a prominent role in determining a community's competitiveness in the world marketplace. In most societies, it is also recognized as a major avenue to greater economic rewards and social mobility, making it of vital importance to those groups on the bottom of the socioeconomic ladder of society. The provision of public educational services to the Negev Bedouin, admissions procedures and standardized testing, financial assistance policies, and the socio-economic and political impact of higher education in Israel are examined in-depth. The paper concludes that the following structural and policy changes are needed to improve the access of the Negev Bedouin community to higher education: better quality elementary and secondary education, financial aid, removal of minimum age requirements, and culturally unbiased measures for admissions screening.